Deep Ultraviolet, Emission-line Imaging of the Makani Galactic Wind - Triet Ha; David S. N. Rupke; Shane Caraker; Jack Harper; Alison L. Coil; Miao Li; Christy A. Tremonti; Aleksandar M. Diamond-Stanic; James E. Geach; Ryan C. Hickox; Sean D. Johnson; Gene C. K. Leung; et al. (The Astrophysical Journal)
The O vi 1032, 1038 Å line is a key probe of cooling gas in the circumgalactic medium (CGM) of galaxies but has been observed to date primarily in absorption along single sight lines. We present deep Hubble Space Telescope (HST) Solar Blind Channel of the Advanced Camera for Surveys observations of the compact, massive starburst Makani. Makani hosts a 100 kpc, [O ii ]-emitting galactic wind driven by two episodes of star formation over 400 Myr. We detect O vi and Ly α emission across the [O ii ] nebula with similar morphology and extent, out to r ≈ 50 kpc. Using differential narrowband imaging, we separate Ly α and O vi and show that the O vi emission is comparable in brightness to [O ii ], with L _O VI = 4 × 10 ^42 erg s ^−1 . The similar hourglass morphology and size of [O ii ] and O vi implicate radiative cooling at T = 10 ^5.5 K in a hot–cold interface. This may occur as the T > 10 ^7 K CGM—or the hot fluid driving the wind—exchanges mass with the T ≈ 10 ^4 K clouds entrained in (or formed by) the wind. The optical/UV line ratios may be consistent with shock ionization, although uncertain attenuation and Ly α radiative transfer complicate the interpretation. The detection of O vi in Makani lies at the bleeding edge of the UV imaging capabilities of HST and provides a benchmark for future emission-line imaging of the CGM with a wide-area UV telescope.